En coup de sabre linear scleroderma with central nervous system involvement in a pediatric patient - Kulikova, S L; Semashko, M D; Levshuk, O N; Siz, M A; Antonenko, D A (Zhurnal nevrologii i psikhiatrii imeni S.S. Korsakova, 2025)
Juvenile localized scleroderma (JLS) is a rare chronic inflammatory disease of connective tissue characterized by inflammation and fibrosis of the skin and underlying tissues, in some cases involving the fascia, muscles, bones, and central nervous system. This paper presents a clinical case of a 5-year-old female patient with en coup de sabre linear scleroderma. Three years after the onset of skin manifestations, she developed a stroke-like syndrome with acute left-sided hemiparesis and three focal epileptic seizures in the first week after the hemiparesis occurrence. Magnetic resonance imaging revealed cystic lesions and white matter changes in the right hemisphere of the brain, specifically at the level of the basal ganglia and the frontal lobe. There were no findings in the diffusion weighted imaging (DWI) mode typical for an acute cerebrovascular accident. According to the electroencephalogram, periodic rhythmic deceleration was recorded in the fronto-central-temporal leads of the right hemisphere. Neurological deficit resolved within three weeks. Epileptic seizures were not repeated with levetiracetam therapy at a dose of 20 mg/kg/day during the follow-up period for two years. To date, few cases of patients with localized scleroderma of the face and scalp involving the nervous system have been described. No treatment guidelines have been developed yet. Further research is needed to improve diagnosis and establish the optimal treatment approach.